'Time to figure out what to do': understanding the nature of Irish post-primary students' interactions with computer-based exams (CBEs) that use multimedia stimuli. Issue 1 (2nd January 2022) - Lehane, Paula; Scully, Darina; O'Leary, Michael
ABSTRACT: In line with the widespread proliferation of digital technology in everyday life, many countries are now beginning to use computer-based exams (CBEs) in their post-primary education systems. To ensure that these CBEs are delivered in a manner that preserves their fairness, validity, utility and credibility, several factors pertaining to their design and development will need to be considered. This research study investigated the extent to which the design of different types of test items (e.g. inclusion of multimedia stimuli) in a CBE can affect test-takers' engagement and behaviour. Qualitative data from a cued-Retrospective Think Aloud (c-RTA) protocol were gathered from 12 participants who had participated in a previous eye-tracking study. Participants watched a replay of their eye movements and were asked to state out loud what they were thinking at different points of the replay. Thematic analysis of the responses from these cognitive interviews captured the nature of students' interactions with online testing environments under three main themes: Familiarisation, Sense-making and Making Decisions. Students also provided their opinions of and recommendations for the future of Irish online assessments. These findings can offer guidelines to all stakeholders considering the use of CBEs in post-primary contexts.